Traffic Conflict Management Strategies at Intersections in Makassar City - Mallawangeng, Tamrin; Yusuf, Andi Rumpang; Nur, Achmad Irfan; Cangara, Iin Fitrianty Suaib (Engineering, Technology & Applied Science Research, 2026)
This study focuses on assessing traffic characteristics at four crossroads in the city of Makassar, employing a quantitative descriptive methodology. The analyzed parameters include traffic volume, road capacity, free flow speed, degree of saturation, road service level, and types and locations of traffic conflicts. The results indicate that the highest traffic volume occurs on crossings at each intersection, peaking on weekdays, particularly on Monday mornings. Most crossings are classified at road service level A, with a few of them placed in category B due to high Volume-to-Capacity (V/C) ratio. Traffic conflicts are caused by merging and crossing, influenced by driver behavior, vehicle type, and environmental conditions. Adaptive traffic light control, enhanced geometric designs, and road markings are thus required to reduce traffic congestion and enhance safety at crossings. The present study contributes to the development of efficient traffic control strategies in a metropolitan environment.